The Impacts of Economic and Political Drivers on the Performance of the Chinese Fintech Sector: The Mediating Role of Blockchain Developments - Xie, Pengyan; Kassim, Aza Azlina Md; Wei, Mingxia; Helmi, Rabab Alayham Abbas (Migration Letters, 2023)
The emergence of finance technologies (fintech) has revolutionised traditional financial services and delivery processes, the advancement of blockchain technologies has aided the transition of fintech services with optimized efficiency and added values for modern customers. This study critically explored the impacts of macroeconomic environment factors and policy interventions in China on the developments of blockchain across the period of 2017 to 2021, examining how blockchain developments (BDI) mediate the relationship between economic driver influence (EDI), political driver influence (PDI) and Chinese fintech market performance (CFMP). This study contributed to literature gap and utilised empirical knowledge on the measurement of macroeconomic and political factors toward technological development, forming designated proxies and latent variables to offer new parameters to measure the influence of these factors in unified manners. This study measured economic driver influence under GDP per capita (GDP), gross national income (GNI), government borrowing and debt (GBD), gross domestic expenditure on R&D per capita (GERD) and labour cost index (LCI), political factor influence is measured under government funding (GF), pilot zones (PZ), incubators (IC), national champions (NC) and supportive policies by engaged province ratio (SP). Blockchain development is measured by the number of blockchain company registrations (BCR), blockchain patents (NBP), venture capital investment volume (VCI) and revenue of blockchain companies (RBC). The results reveal that both EDI and PDI have highly statistically significant relationships with BDI, positively impacting the growth of the overall Chinese fintech market sector and across 4 key fintech segments of alternative finance, digital assets/ investments and payments.